Selecting Parameters of Detectors When Recognizing Materials Based on the Separation of Soft and Hard X-Ray Components; Russian Journal of Nondestructive Testing; Vol. 54, iss. 11 - Osipov S. P. Sergey Pavlovich; Usachev E. Yu. Evgeny Yurjevich; Chakhlov S. V. Sergey Vladimirovich; Shchetinkin S. A. Sergey Aleksandrovich; Kamysheva E. N. Ekaterina Nikolaevna (2018, 2018)
Title screen